PENGURANGAN PEMAKAIAN SAMPAH PLASTIK SEKALI PAKAI BAGI GENERASI MUDA MELALUI PROGRAM BRING YOUR TUMBLER GOES TO SCHOOL - K. A. Sudiarawan; P. A.H. Martana; T. I.D.W.P. Dewi; P. D.Y. Utami; I. K.W. Dwipayana; I. K.W. Putra (Buletin Udayana Mengabdi, 2022)
The problem of managing plastic waste that has a significant impact on environmental quality makes this dedication carried out with the aim that the "Bring Your Tumbler Goes to School Movement" can be carried out in order to reduce plastic waste circulating in the community. The results of this dedication that using preliminary research methods, providing socialization and support facilities has proven to have a significant impact in daily life for students of SMP N 4 Marga. This dedication activity has concluded that the “Bring Your Tumbler Goes to School” is following the program’s objectives such as a form of implementation related to the management and reduction of plastic waste as well as strengthening the character and awareness of the younger generation to love the environment by using tumbler instead of using disposable bottles. The meaning of this dedication is to build the character of the younger generation on the importance of loving the environments for our better life. Keywords: Environment, Plastic Waste, Bottled Water